Spectral analysis of the discoloration process in architectural electrochromic glass - Jianan Wen; Xi Meng (Scientific Reports)
Abstract Electrochromic glass has been widely employed in buildings, due to its favorable thermal performance, optical properties and adjustability, and more attention was paid to its final states of bleached and tinted on the building thermal performance. However, because of the contradiction between visual and thermal environment, there must be their suitable balance, which the certain state between bleached and tinted, not the final states. To find this certain state and thereby, improve the application efficacy of electrochromic glass, a detail and transient spectral analysis must be done during the whole coloring and fading processes. Under this condition, an optical experiment platform was designed to test the transmittance, reflectance and absorbance of the electrochromic glass under the wavelength from 380 nm to 2500 nm.The experimental results showed the visible light regulation of electrochromic glass is mainly focused on the warm light spectrum between 500 nm and 700 nm. In the near-infrared region, the regulation of electrochromic glass to light is mainly concentrated in the 780–1400 nm range, with relatively minimal adjustment observed for other wavelengths of light. For electrochromic glass, the regulation range of global transmittance, reflectivity and absorptivity are 0.3–45.4%, 3.6–5.8% and 49.5–95.3% under the visual lights from 380 nm to 780 nm, while they are 2.6–31.9%, 3.46–5.18% and 63.2–93.3% under the near infrared lights from 780 nm to 2500 nm. The transmittance of electrochromic glass is primarily altered through the adjustment of the absorbance. This test provides the corresponding curves of the optical properties of electrochromic glass in the visible and near-infrared range, as well as the fitted curves of transmittance, reflectivity and absorptivity in the near-infrared range of the optical properties with the change of visible light. The curves are not related to the direction of discoloration, but only to the state of the glass. This article provides data that may be used to support the search for the light-heat balance of electrochromic glass in architectural applications.